Etika Aparatur Sipil Negara dalam Membangun Good Governance - Tulus Santoso; Maya Puspita Dewi (Institut Ilmu Sosial dan Manajemen STIAMI, 2019)
Civil servants as a government apparatus are required to have ethics. However, the phenomenon of many civil servants being convicted of corruption and still receiving salaries, even filed a lawsuit, left a big question mark regarding their compliance with ethics. The method used in this paper is a literature study. The results showed that corruption is a violation of ethics and the reluctance to resign and even sue when dismissal is clearly contrary to ethical behavior. Legal norms as a manifestation of ethics in the form of written law and an embodiment of good governance are good enough, it's just that law enforcement must be done by superiors, Staff Development Officers are not done and they become part of those who also violate ethics because they do not want to uphold ethics in his environment. This also is not in line with the spirit of good governance that not only wants the rule of law but also must have law enforcement. In the future, as an effort to create ethical Civil Servants, law enforcement must be carried out absolutely.